The level of independence and the level of life satisfaction among the elderly: a Cross-sectional study in Nursing Home - Fahruddin Kurdi; Anggraini Probowati; Niken Asih Laras Ati (Journal of Health, Sport, and Nursing, 2025)
Elderly people will experience physical, psychosocial, and cognitive changes due to aging. These changes make the elderly at high risk of losing functional abilities, reducing their independence in daily activities and becoming dependent on others. The decline in the ability of the elderly to perform daily activities affects their quality of life and life satisfaction. This study aimed to analyze the correlation between the level of independence and the level of life satisfaction among the elderly at nursing home of Jember. This study used a cross-sectional design with total sampling on 73 respondents. The Katz Index was used to identify the level of independence, and the Satisfaction with Life Scale (SWLS) was used to identify the level of life satisfaction among the elderly. Data were analyzed using the Kendal Tau-C test. The results showed that the majority of the elderly were independent (83.6%) and had a slightly satisfied life satisfaction (37.0%). Based on the results of this study, there was a correlation between the level of independence and the level of life satisfaction among the elderly at nursing home of Jember (p-value=0.024; r=0.750). It can be concluded that the higher the level of independence, the higher the life satisfaction of the elderly. Therefore, the elderly must maintain their health and physical activity regularly to prevent significant physical decline. The role of nurses/caregivers is to provide assistance to the elderly according to their abilities and pay attention to their social and spiritual needs.